Implementation Of The K-Means Clustering Algorithm For Grouping Heart Disease Risk Levels - Sonia Indhira; Billy Hendrik (Lembaga Pengembangan Kinerja Dosen, 2023)
Heart disease is a condition where the heart cannot carry out its duties properly, this disease occurs when blood to the heart muscle stops or becomes blocked, causing serious damage to the heart. The KMeans algorithm can be used to cluster heart disease groups to find out if someone is affected heart disease or not. The clustering method with the k-means algorithm in this research shows a new insight, namely grouping the risk level of heart disease based on 3 clusters. Cluster 1 is a category age with a fairly low risk level for heart disease or Low, namely 355 out of 1025 age categories tested, then cluster 2 is the age category with a moderate risk level for heart disease, namely 208 out of 1025 age categories tested, and finally cluster 3 is an age category with a fairly high age category level or High, namely 462 of 1025 age categories tested.